Shariah Governance and Audit Practices in Islamic Co-operatives: An Audit Expectation-performance Gap Analysis - Supiah Salleh; Muhammad Iqmal Hisham Kamaruddin; Zurina Shafii; Mustafa Mohd Hanefah; Nurazalia Zakaria; Wan A’tirah Mahyudin; Nur Amni Mahmud Sabri (Virtus Interpress, 2024)
Indexed by Scopus